2020
DOI: 10.1155/2020/9358542
|View full text |Cite
|
Sign up to set email alerts
|

Broad Diversity of Fungi in Hospital Water

Abstract: Introduction. Some studies have reported the occurrence of microorganisms isolated from water. Considering these microorganisms, fungi are known to occur ubiquitously in the environment, including water, and some are pathogenic and may cause health problems, especially in immunocompromised individuals. The aim of this study was to identify fungi in hospital water samples and to correlate their presence with the concentration of free residual chlorine. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Aspergillus, Byssochlamys, Candida, Cephalosporium, Cladosporium, Fusarium, Mucor, Penicillium, Rhizopus, Saccharomyces, Sporobolomyces and Trichoderma were reported by Obire et al, (2009). Arroyo et al, (2020) also reported the presence of Aspergillus sp, Fusarium sp and Penicillium sp from hospital water which are also similar to the fungal isolates in the present study. Although in their study, Cladosporium sp was the most common fungal isolate with wide distribution followed by Penicillium sp while in the present study, Penicillium sp was the most common fungal isolates followed by Aspergillus.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Aspergillus, Byssochlamys, Candida, Cephalosporium, Cladosporium, Fusarium, Mucor, Penicillium, Rhizopus, Saccharomyces, Sporobolomyces and Trichoderma were reported by Obire et al, (2009). Arroyo et al, (2020) also reported the presence of Aspergillus sp, Fusarium sp and Penicillium sp from hospital water which are also similar to the fungal isolates in the present study. Although in their study, Cladosporium sp was the most common fungal isolate with wide distribution followed by Penicillium sp while in the present study, Penicillium sp was the most common fungal isolates followed by Aspergillus.…”
Section: Resultssupporting
confidence: 89%
“…Pfaller and Diekema (2004) opined that these dematiaceous fungal isolates are the major cause of mycoses and other types of infections including cutaneous, subcutaneous, invasive, and contagious infections. More so, fungal genera such as Aspergillus, Fusarium, Mucor, Penicillium, etc are known mycotoxin producers (Prescott et al, 2011) and consumption of mycotoxins could lead to mycosis and vascular diseases (Arroyo et al, 2020). Most of the isolated fungal genera contain species that are potential pathogens or opportunistic pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding fungi, the ones we isolated in pure culture belonged to the genera Aureobasidium (five isolates), Ustilago , Cystobasidium , Rhodotorula and Cryptococcus (the last four represented by just one isolate). Despite the low number of fungal isolates selected, the fact that the yeast genera Aureobasidium , Rhodotorula and Cryptococcus had previously been reported to inhabit different hospital facilities is in accordance with our results 67 .…”
Section: Discussionsupporting
confidence: 91%
“…These outbreaks resulted in a total of 31 patient infections, with 3 fatalities. The primary cause of the outbreaks was contamination of the water supply pipes [ 10 ]. Some patients have died from infection with Legionella in the waterway during dental visits; a female patient succumbed to Legionnaires’ disease after receiving dental treatment.…”
Section: Introductionmentioning
confidence: 99%